Revolutionary prophecies : the founders and America's future - McDonald, Robert M. S., 1970-; Onuf, Peter S. (Jeffersonian America., 2021)
"Collections of essays often struggle to cohere, but the thesis of "Revolutionary Prophecies" is clear. Traditionally, the term "revolution" suggested circular motion: the rise and fall of classical republics and modern dynasties followed the same inevitable pattern. The American Revolution promised to change everything, liberating a newly self-conscious and self-governing people from the thralldom of foreign despotism. As the circle became a line, the people could envision a future for their grandchildren's grandchildren, stretching across the generations to a distant horizon. The essays in "Revolutionary Prophecies" hone in on a diverse cast of characters from the Founding generation-luminaries like George Washington, John Adams, Benjamin Franklin, Alexander Hamilton, James Madison, and James Monroe, but also less prominent people such as printer and antiquarian Isaiah Thomas, backcountry rebels, and American Indians. All of them, in different ways, reveal that how we understand the past and present shapes our hopes, ambitions, and anxieties about the future"--